Effects of exenatide therapy on insulin resistance in the skeletal muscles of high-fat diet and low-dose streptozotocin-induced diabetic rats. (2nd January 2016) - Wu, Hui; Sui, Chunhua; Xia, Fangzhen; Zhai, Hualing; Zhang, Huixin; Xu, Hui; Weng, Pan; Lu, Yingli
Abstract: Purpose : The glucagon-like peptide (GLP)-1 agonist exenatide shows the same multiple effects on glucose homeostasis as native GLP-1, which can reduce blood glucose levels in individuals with type-2 diabetes mellitus (T2DM). However, its underlying action mechanism on glucose metabolism in the skeletal muscle of T2DM cases is unknown. We investigated the effects and action mechanisms of exenatide on insulin resistance (IR) in the skeletal muscle of high-fat diet and low-dose streptozotocin-induced T2DM rats. Methods : Four groups of Sprague–Dawley rats were studied: non-T2DM (control, C); non-T2DM + exenatide (C + E); T2DM (D); and T2DM + exenatide (D + E). After eight weeks, isotope-tracer methodology was applied to measure the total rate of appearance (Ra) of glucose and glucose infusion rate (GIR) using a hyperinsulinemic–euglycemic clamp with 3- 3 H-glucose infusion. Glucose uptake in gastrocnemius muscles was determined by measuring 2-deoxy-D- 14 C-glucose radioactivity. Simultaneously, ultrastructural changes in the cells of gastrocnemius muscles were studied. Results : In the D + E group, body weight and levels of fasting plasma glucose, triglyceride, total cholesterol, low-density lipoprotein and insulin were decreased significantly ( p < 0.01) compared with the D group. The Ra of glucose (94.70 ± 13.46 versus 121.07 ± 16.55 μmol/kg/min) was decreased ( p < 0.01), whereas the exogenous GIR (144.68 ± 11.03 versus 114.50 ± 9.40 μmol/kg/min) and glucose uptake in muscle (0.24 ± 0.02 versus 0.17 ± 0.02 μmol/g/min) were increased markedly ( p < 0.01). Ultrastructural observations revealed that exenatide attenuated the effect of swollen mitochondrial and endoplasmic reticulum within the cells of the skeletal muscle of T2DM rats. Conclusions : These data suggest that exenatide can significantly improve insulin sensitivity in skeletal muscle by increasing glucose uptake in T2DM rats.